Editor's Choice – Focused Update on Patients Treated with the Nellix EndoVascular Aneurysm Sealing (EVAS) System from the European Society for Vascular Surgery (ESVS) Abdominal Aortic Aneurysm Clinical Practice Guidelines. (March 2023) - Boyle, Jonathan R.; Tsilimparis, Nikolaos; Van Herzeele, Isabelle; Wanhainen, Anders; ,; Bastos Gonçalves, F.; Bellmunt, S.; Berard, X.; D'Oria, M.; Fernandez, C.; Karkos, C.; Kazimierczak, A.; et al.
Abstract : Objective: After alerts on EndoVascular Aneurysm Seal (EVAS) failure were raised, the European Society for Vascular Surgery (ESVS) Abdominal Aortic Aneurysm (AAA) Clinical Practice Guidelines Writing Committee (WC) initiated a task force with the aim to provide guidance on surveillance and management of patients with implanted EVAS devices. Methods: Based on a scoping review of risk for late serious aortic-related adverse events in patients treated with EVAS for AAA, the ESVS AAA Guidelines WC agreed on recommendations graded according to the European Society of Cardiology (ESC) grading system. Results: EVAS has a very high incidence of late endograft migration resulting in proximal type 1 endoleak with risk of rupture, requiring open conversion with device explantation. The reported mortality rate for elective explantation varies between 0% and 14%, while acute conversion for rupture has a very dismal prognosis with a 67 – 75% mortality rate. Conclusion: It is recommended that all patients in whom a Nellix device has been implanted should be identified, properly informed, and enrolled in enhanced surveillance. If device failure is detected, early elective device explantation should be considered in surgically fit patients.